Implementation of The Islamic Character Building (ICB) Program as an Alternative Model of Islamic Religious Education in Shaping The Islamic Character of Students at Sma Islam Plus Adzkia Medan - Filia Bunga Syahbrina; As’ad As’ad (FKIP - Universitas Riau, 2026)
The increasingly worrying practice of free association and social life, especially among adolescents, is caused by some members of society being disoriented in living their lives. This study aims to examine the implementation of the Islamic Character Building Program (KMA) at SMA Islam Plus Adzkia Medan as a form of renewal in the general Islamic Religious Education curriculum to shape Islamic character in students. This study uses a qualitative approach with a case study design to analyze the implementation strategy, obstacles encountered, and the program's success rate in shaping student character. The results show that the success of the KMA program is supported by three main factors: strengthening the emotional bond between educators and students, the use of daily journals as a means of self-reflection, and a personal approach in addressing behavioral problems. On the other hand, this program faces obstacles in the form of the strong influence of digital media and consumer culture among students. The implications of these findings contribute both theoretically and practically to the development of Islamic-based character education amidst the challenges of character education in the digital era and the weaknesses of conventional Islamic Religious Education learning.